The gesture : movement in painting and sculpture - Morgan, Robert C. (New York : Neuhoff Gallery, 2002)
Suvero, Mark di ; Goldberg, Michael ; Gu Wenda ; Kline, Franz ; Machado, Gabriela ; Ming-Chip, Fung ; Miotte, Jean ; Mitchell, Joan ; Motherwell, Robert ; Nares, James ; Neff, Stacey ; Rim, Jungwook Grace ; Soong, Path ; Stella, Frank ; Twombly, Cy ; Venet, Bernar
biog. p. 46-61
Engels
The gesture : movement in painting and sculpture, Neuhoff Gallery, New York, from September 17th through October 19th, 2002
boek